Uma proposta de regra de reajuste aplicada a planos de benefícios definidos - Amaro, Rômulo Pereira (2012)
Taking as premise the need to make retirement plans structured in Defined Benefit (DB) and Hybrid (combination of a Defined Benefit Plan and Defined Contribution) under Private Pension, more attractive to sponsors and thereby reduce the use of model Defined Contribution (DC) commonly adopted in Brazil, considered by many scholars in the field not interesting to participants of benefit plans due to not effectively meet the purpose of social security, is presented in this study a proposal for readjustment rule of benefits that can be adopted both in DB plans as well as in Hybrid, but that relies on DC plans logic. It is an intermediate readjustment rule between the ones commonly adopted in DB plans and DC plans. Through this new rule, the benefits readjustment will be based on investments cumulative profitability, ranging from 0 to 100% of inflation, with the possibility of recovering inflationary losses in situations which investment performance exceeds the actuarial target. In order to demonstrate the viability of the proposed readjustment rule, results of a simulation study using the Monte Carlo method are presented, comparing benefits readjustment based on inflation rate (100% inflation) and readjustment based on the new rule. Simulation results point to possible lower difference, in 60 years, around 10% of benefit net value calculated on the new rule. Although new rule’s adoption could result in reduction of the net benefit when compared with inflation-based readjustment rule, it appears more advantageous to the participant when compared with readjustment rule practiced in DC plans because it does not admit application of negative annual readjustment on benefits. The proposed rule establishes a point of convergence for both participants and sponsors interests. The readjustment mechanism here proposed represents an innovation to the Brazilian Private Pension system.